Optimized dynamic response of parallel operation of two single phase inverters based on evolutionary theory - Godoy, R. B. [UNESP]; Canesin, C. A. [UNESP]; Pinto, J. O P (Institute of Electrical and Electronics Engineers (IEEE), 2010)
In this work it is proposed an optimized dynamic response of parallel operation of two single-phase inverters with no control communication. The optimization aims the tuning of the slopes of P-ω and Q-V curves so that the system is stable, damped and minimum settling time. The slopes are tuned using an algorithm based on evolutionary theory. Simulation and experimental results are presented to prove the feasibility of the proposed approach. © 2010 IEEE.
Keywords: Inverters; Modeling; Optimization; Parallel operation; Control communications; Evolutionary theories; Parallel operations; Settling time; Single-phase inverters; Dynamic response; Power electronics; Curve fitting